Sinus Optimization Method for Multi Reservoir Operation by Using Multipurpose Simulation Model - Ahmadi, Yudha T.; Sholichin, Moh.; Limantara, Lily M.; Asmaranto, Runi (Civil Engineering Journal, 2026)
This research intends to apply the multiplication sinus method to optimize two parallel reservoirs, namely the Tugu and Bagong reservoirs, in order to increase the efficiency of multipurpose water resource utilization for irrigation, raw water supply, micro-hydro electrical power (PLTMH), and flood control. The methodology consists of optimizing water allocation during low-flow conditions for the two parallel reservoirs with multiple purposes. For irrigation, the multiplication sinus method is used, while the other purposes are optimized using a simulation model with the objective function of maximizing the net benefit. Meanwhile, flood control under high-flow conditions is addressed through simulation by optimizing gate openings. The results show that the strategy of valve opening at the initial stage of a flood event significantly reduces the volume of flood storage required. This makes it possible to increase the reservoir water level, thereby directly increasing the potential of water energy without exceeding the river channel capacity downstream. Specifically, in the Tugu reservoir, flood storage is reduced from 1.8 million m³ to 1.3 million m³, with a peak discharge of 124.5 m³/s, which remains below the downstream river capacity (approximately 125 m³/s). Meanwhile, in the Bagong reservoir, flood storage can be reduced from 5.2 million m³ to 4.3 million m³, with a peak discharge of 41.9 m³/s, which is still safe and below the river capacity (approximately 44 m³/s). This efficiency proves that coordinated flood management between two parallel reservoirs can be carried out without sacrificing other interests. From the economic benefit perspective, the annual total value generated by the Tugu reservoir reaches a maximum of Rp. 136 milliard and a minimum of Rp. 117 milliards, with the main contribution coming from irrigation water supply. Likewise, the Bagong reservoir produces the highest annual benefit of Rp. 93.5 milliard and the lowest of Rp. 83.7 milliard, which comes entirely from irrigation.